1995
DOI: 10.1007/bf01420070
|View full text |Cite
|
Sign up to set email alerts
|

Do the suprasellar neurenteric cyst, the Rathke cleft cyst and the colloid cyst constitute a same entity?

Abstract: Two cases of entirely suprasellar cysts are reported. Total surgical removal was performed in both cases. Pathological and immunohistochemical profiles were consistent with neurenteric cysts, Rathke's cleft cysts or colloid cysts and was also in keeping with an endodermal origin. It is now admitted that these three kinds of cysts share similar histological and immunohistological features. We propose an hypothesis of common embryological origin from endodermal remnants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
67
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 48 publications
1
67
0
1
Order By: Relevance
“…1 7 Neurenteric cysts stain positive for cytokeratin markers, and are negative for neuronal and ectodermal markers such as GFAP, S-100, neuron specific enolase and synaptophysin. 3,13,14 Neurenteric cysts are usually, but not always, positive for CEA which is a marker of the embryonic gastrointestinal tract. 2 , 1 4 Ependymal cysts react positively for GFAP and negative for cytokeratin and CEA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 7 Neurenteric cysts stain positive for cytokeratin markers, and are negative for neuronal and ectodermal markers such as GFAP, S-100, neuron specific enolase and synaptophysin. 3,13,14 Neurenteric cysts are usually, but not always, positive for CEA which is a marker of the embryonic gastrointestinal tract. 2 , 1 4 Ependymal cysts react positively for GFAP and negative for cytokeratin and CEA.…”
Section: Discussionmentioning
confidence: 99%
“…17 Different explanations for their formation have thus been proposed. Graziani et al 14 suggested that suprasellar neurenteric cysts, Rathke's cleft cysts, and colloid cysts arise from Seessel's pouch which is an outpouching of the oropharyngeal membrane in the 42-day-old embryo. 14 S e e s s e l 's pouch regresses in humans but forms the adenohypophysis in inferior vertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations